HYPOPHOSPHATASIA, RARE BONE MINERALISATION DISORDER THAT MIMICS OSTEOGENESIS IMPERFECTA AT BIRTH - Nordin, Farah Nursyahirah Binti (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Hypophosphatasia is a genetic disorder characterized by impaired mineralization of bones and teeth that results in fractures and deformities. It affects less than 1:100,000 live births with different clinical spectrums. It is caused by loss-of-function mutations of ALPL gene that encodes tissue nonspecific alkaline phosphatase (TNSALP), leading to low activity of this enzyme that usually mediates the breakdown of inorganic pyrophosphate that blocks mineralization. We reported an infant who was initially admitted to NICU at birth. CASE Antenatally, the patient was detected with possible osteogenesis imperfecta and unilateral lung hypoplasia by a detailed foetal scan at 32 weeks gestation. His mother had GDM and underwent LSCS at 37 weeks 5 days with a weight of 2.42 kg. He was born with generalized bowing deformities of both upper and lower limbs, a broad forehead, wide wide-spaced nipple, and no blue sclera. His respiratory assessment was normal. His skeletal survey reported generalised osteopenia with bowed limbs and plastic fracture over the right femur consistent with osteogenesis imperfecta. He had normal serum calcium, persistently low ALP (18-25 IU/L), iPTH: 69.3 pg/ml (14.9- 56.9) and 25 (OH) vit D3: 51.70 nmol/L (insufficient). There was no family history of bone diseases and parents were not consanguineous. His genetic results showed heterozygous, autosomal recessive, likely pathogenic, ALPL (NM_000478.6), Exon 2, c.29T>C, p. (Ile10Thr), and ALPL (NM_000478.6), Exon 9, c.991G>A, p. (Val331Met). He continued to improve without treatment and was last reviewed at 5 months old, with appropriate development and no fracture. CONCLUSION There are very few cases of hypophosphatasia reported locally. It is important to highlight the differential as compared to osteogenesis imperfecta. Hypophosphatasia could present differently, with our case reflecting the benign perinatal type, whereas others would require enzyme replacement, or asfotase-alfa as the first medical treatment for perinatal, infantile and juvenile onset of the disease.